Barriers to Uptake of Cataract Surgery in Central Chhattisgarh - Samrat Chatterjee; Nehal Mohata; Anil Babanrao Gangwe; Anupam Sahu; Deepshikha Agrawal (Indian Journal of Public Health)
Background: Understanding and addressing barriers to cataract surgery is important in increasing cataract surgical coverage. Barriers differ across time and place; therefore, periodic evaluation in the area of operation of an eye care provider is required. Objectives: The objective is to enumerate the barriers to cataract surgery in central Chhattisgarh. Materials and Methods: A hospital-based cross-sectional study was carried out among community outreach patients with cataract in 2022. Patients were selected through systematic random sampling. Results: Of the 2210 patients, 1026 completed the survey. Overall person-related barriers (65.3%) were more common than service-related barriers (34.7%). The different barriers were lack of escort (34.0%), cost of surgery (17.7%), lack of awareness of cataract (9.6%), fear of losing eyesight (6.8%), unfelt need (6.3%), waiting for outreach camp to happen in a close-by location (5.9%), waiting for the cataract to mature (4.6%), do not know where to go (3.9%), busy with work (3.7%), living far from the hospital (1.9%), need not felt - old age (1.7%), blindness is God’s will (1.4%), other health reasons (1.1%), being female (0.8%), and village not connected to the main road/lack of transport (0.6%). Person-related barriers were more common (P < 0.05) in female patients, illiterate patients, and those from a lower socio-economic class. Fear of losing eyesight was the most common barrier in patients who had poor vision following cataract surgery in the other eye. Conclusion: Person-related barriers were more common than service-related barriers for accessing eye care services. Important service-related barriers were the cost of surgery and lack of awareness about cataract.